2021
DOI: 10.1111/tpj.15159
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide occupancy of Arabidopsis SWI/SNF chromatin remodeler SPLAYED provides insights into its interplay with its close homolog BRAHMA and Polycomb proteins

Abstract: SUMMARY SPLAYED (SYD) is a SWItch/Sucrose Non‐Fermentable (SWI/SNF)‐type chromatin remodeler identified in Arabidopsis thaliana (Arabidopsis). It is believed to play both redundant and differential roles with its closest homolog BRAHMA (BRM) in diverse plant growth and development processes. To better understand how SYD functions, we profiled the genome‐wide occupancy of SYD and its impact on the global transcriptome and trimethylation of histone H3 on lysine 27 (H3K27me3). To map the global occupancy of SYD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 72 publications
(127 reference statements)
4
38
0
Order By: Relevance
“…The fact that TPF contains 3xPHD and Tudor domains, previously shown to interact with methylated and acetylated histones (49,50,78), makes these two histone marks likely direct targets of TPF proteins to promote recruitment or stability of the complex on target sites. On the contrary, the complex was not found over facultative or constitutive heterochromatic regions, similar to what was observed for BRM and SYD targets, indicating that plant SWI/SNF complexes do not normally localize to these regions (38,39,76). Interestingly, BRM and SYD have been shown to play antagonistic and synergistic interactions with the Polycomb complex, responsible for the deposition of the facultative heterochromatic mark H3K27me3 (7981).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The fact that TPF contains 3xPHD and Tudor domains, previously shown to interact with methylated and acetylated histones (49,50,78), makes these two histone marks likely direct targets of TPF proteins to promote recruitment or stability of the complex on target sites. On the contrary, the complex was not found over facultative or constitutive heterochromatic regions, similar to what was observed for BRM and SYD targets, indicating that plant SWI/SNF complexes do not normally localize to these regions (38,39,76). Interestingly, BRM and SYD have been shown to play antagonistic and synergistic interactions with the Polycomb complex, responsible for the deposition of the facultative heterochromatic mark H3K27me3 (7981).…”
Section: Discussionsupporting
confidence: 75%
“…This location is shared by other SWI/SNF chromatin remodeling proteins in animals, and fungi (74,75). Studies of the genomic location of the BRM and SYD ATPases revealed their location over TSS regions of many genes (38,39,76), pointing to their colocalization with the BAF-like complex. An open question is whether there is functional crosstalk between the plant BAF-like and ncBAF-like complexes over shared targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoprecipitation of BRM‐GFP successfully isolated the subunits of the SWI/SNF complex in A. thaliana , including SWP73A, SWP73B, SWI3A, SWI3B, SWI3C, SWI3D, and SYD (Li et al, 2016). ChIP‐seq also demonstrated that SYD and BRM targeted a common set of genes under normal conditions (Shu et al, 2021).…”
Section: Roles Of Chromatin Remodelling Factors In Salt Stress Responsesmentioning
confidence: 99%
“…Meanwhile, SYD functions antagonistically with MOS1 and MOS9 at the chromatin level to regulate SNC1 transcription and SNC1-mediated immunity (Johnson et al 2015). Strikingly, the expression levels of SYD were found to be dramatically decreased upon indoleacetic acid (IAA), ABA, and benzothiadiazole (BTH) treatments and increased upon flg22 treatment, which suggests that SYD responds to pathogen attack at the transcription level (Shu et al 2021).…”
Section: Roles Of the Swi/snf Complex In Plant-pathogen Interactionmentioning
confidence: 99%